Consumer’s Satisfaction and Employee’s Job Satisfaction - Widyatmojo, Pribadi; Rahatmawati, Istiana; Karyono (Jurnal Mebis, 2025)
The employee’s job satisfaction and consumer’s satisfaction with fairness or equability is a topic needed by any organization, including a profit-oriented organization, because it influences organizational performance. This research aims to figure out the influence of employees’ job satisfaction and consumers’ satisfaction with fairness or equability on organization performance. Theoretically, the job satisfaction variable serves as an organizational performance variable, as job satisfaction leads to high dedication to organizational performance. This research uses doctors and nurses as research respondents. The analysis result discussed